2010
DOI: 10.1002/htj.20295
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of effective oxygen diffusivity in microporous media containing moisture

Abstract: The mass transfer characteristics of the gas diffusion layer (GDL) are closely related to the cell performance of a polymer electrolyte fuel cell (PEFC). The oxygen diffusivity of paper type porous media, which is generally used as a GDL, was measured with respect to its liquid water content using experimental apparatus consisting of an oxygen sensor based on the galvanic cell. A numerical method was established to obtain the effective oxygen diffusivity of microporous test materials by calculating the oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Park et al [5] found that it was difficult to remove water from CLs employing two materials with different pore sizes. Utaka et al [6,7] devised a method for measuring the oxygen diffusivity of a GDL containing moisture using an oxygen absorber and they evaluated its gas diffusion characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al [5] found that it was difficult to remove water from CLs employing two materials with different pore sizes. Utaka et al [6,7] devised a method for measuring the oxygen diffusivity of a GDL containing moisture using an oxygen absorber and they evaluated its gas diffusion characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A small hole was drilled in the holder to allow air out, but it was closed off during measurements. A vacuum impregnation method [7], in which an evacuated leak-tight container containing the test material is dipped in pure water, was used to saturate the test porous material with water.…”
mentioning
confidence: 99%
“…However, there have been few studies that have measured the effective diffusivity in a sample containing moisture. Through research on water management in PEFCs, the authors have developed a method to measure the oxygen diffusivity of microporous media containing moisture [13,14]. Utaka et al [13] evaluated the gas diffusion characteristics of a dry GDL using a method that employed a galvanic cell oxygen absorber, where multi-layered GDLs with a larger diffusion resistance were used to obtain the precise oxygen diffusivity.…”
Section: Introduction and Summary Of Relevant Former Studiesmentioning
confidence: 99%
“…However, diffusivity measurement of a single GDL containing moisture is required under conditions similar to those during practical operation. The galvanic cell oxygen absorber with peripheral equipment and the measurement method were further improved to evaluate the oxygen diffusion characteristics in a single GDL with/without the presence of moisture [14]. This method was demonstrated to be effective for measuring a single GDL containing moisture and the measurement error factors were also examined.…”
Section: Introduction and Summary Of Relevant Former Studiesmentioning
confidence: 99%
See 1 more Smart Citation